Publicity exploitation of celebrities: protection of a star's style in Quebec civil law - Abramovitch, Susan (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1991)
The use of celebrity imagery, or style, in advertising has become prevalent in recent times. Occasionally advertisers have used photographs of celebrities without having first obtained their consent. The author examines the possible legal bases existing in Quebec civil law which may serve to protect the celebrity against such non-consesual use of his or her picture, drawing on the experience of France, common law in Canada and the United States. Concluding that the right to style is an intellectual property right, the author applies this basis to other instances of style appropriation : the use of voice, sound-alikes, look-alikes and typical expressions.